If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2t = 7 + 4 Combine like terms: 7 + 4 = 11 3 + -2t = 11 Solving 3 + -2t = 11 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2t = 11 + -3 Combine like terms: 3 + -3 = 0 0 + -2t = 11 + -3 -2t = 11 + -3 Combine like terms: 11 + -3 = 8 -2t = 8 Divide each side by '-2'. t = -4 Simplifying t = -4
| -5.6+-0.8y-y=-2 | | x+6+x+3+x+9+x+1+x+1+x+4+x+4= | | 0.5x-3=0.3(2x-3) | | -4.7k=10.81 | | x(13)=104 | | x(5)=55 | | 7t-2(-3t+1)=-3(1-3t) | | 8m-10=62+2m | | -11x+9=185 | | x+2(2)=0 | | 6d+5=-4-3d | | X+(x-355)+(2x+80)=2425 | | 3(-2y)+y=-10 | | 18-x=1 | | y=-16-16 | | -2(3y+4)=20 | | -1/3+1= | | 8y-2y+13=2y+12 | | 5w^2-6w+17=8 | | 6x^3-77x^2+56x+8=0 | | 48y-4(6-y)=12(3y+2) | | -3x-14=1 | | fu=3 | | -7(x+8)=35 | | 175x^2-28=0 | | 3a+9b-12= | | 4x+19=7-2x | | -5+4a+3a+6=0 | | 2x-8y=-34 | | -3(x-4)+10=-2 | | -49+9=-5 | | (7x+2)(3x-y)= |